Odontogenic Maxillary Sinusitis After Tooth Extraction Associated with Dry Socket: A Clinical Case Report - Akhmad Zaida Gresfullah; Febriyani Ayu Wulandari (Jurnal Medali, 2026)
AbstractBackground: Odontogenic maxillary sinusitis (OMS) is a sinus infection of dental origin, commonly associated with extraction of maxillary posterior teeth. While alveolar osteitis (dry socket) is a common post-extraction complication, its progression to OMS is relatively low, though clinically observed. This case report discussed the management of OMS, for the general practitioner to collaborating with otorhinolaryngologist and eliminating the focal infection with non-surgical management.Case: A 28-year-old female presented with severe pain, foul-smelling odor, facial discomfort, and postnasal drip following extraction of the upper left maxillary molar (tooth 26). Clinical examination revealed dry socket, while panoramic radiography suggested sinusitis involvement. Multidisciplinary management, such as saline irrigation, antibiotic therapy, and nasal decongestant under otorhinolaryngologist supervision and for the focal infection included local debridement and curettage without any dressing following with maintaining good oral hygiene. After 12 days, significant symptom improvement was observed, both clinical and radiographic evaluations confirmed complete resolution at three months follow-up. Conclusion: OMS associated with dry socket is relatively low but can be effectively managed with non-surgical multidisciplinary management. Good healing following extraction to eliminate the focal infection is fundamental. Ensuring a favorable prognosis further requires accurate diagnosis, appropriate pharmacological therapy, effective dental focal management, and comprehensive patient education